Behaviour of Value Stocks versus Growth Stocks: An Evidence for Indian Stock Market - A, Balakrishnan A balki (Journal of Contemporary Research in Management (JCRM), 2016)
In this paper, we examine whether value stocks are able to outperform growth stocks in terms of producing significant returns.  We also evaluate the ability of one factor CAPM and two factor model of capturing average returns on portfolios.  We observe from the results that there is a strong value effect in Indian stock market particularly when one forms portfolio based on PB and PE ratios.  On the other hand, weak negative value effect is found in portfolios based on EPS and DY.  The empirical results show that both CAPM and two factor model do not explain the average returns on portfolios.